1987
DOI: 10.1111/j.1600-0773.1987.tb01715.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methyl Mercury on Testicular Functions in Macaca fascicularis Monkeys

Abstract: These studies were performed to investigate the effects of MeHg on testicular function in Macaca fascicularis monkeys. In an in vivo study involving oral treatment of adult males Macaca fascicularis monkeys with MeHg for 20 weeks, changes in spermatozoal production, motility and morphology and in serum testosterone were followed before, during and after treatment. MeHg treatment significantly decreased % motile spermatozoa and scores for sperm speed and forward progression and increased % abnormal sperm tail f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 21 publications
0
32
1
Order By: Relevance
“…Changes include decreases in the diameter of seminiferous tubules, disorganization of the basal membrane and aspermatogenesis. These alterations were reported in different animal species [Chowdhury and Arora 1982], including fish [Friedmann et al 1996;Wester and Canton 1992], birds [McNeil and Bhatnagar 1985;Maretta et al 1995], mice [Lee and Dixon 1975;Orisakwe et al 2001], rats [Massanyi et al 2007;Homma-Takeda et al 2001] and monkeys [Mohamed et al 1987]. It is important to stress that although some data is available on the effects of inorganic mercury on fertility in experimental animals [Lee and Dixon 1975;Orisakwe et al 2001;Rao 1989] the majority of works have focused on organic mercury.…”
Section: Discussionmentioning
confidence: 99%
“…Changes include decreases in the diameter of seminiferous tubules, disorganization of the basal membrane and aspermatogenesis. These alterations were reported in different animal species [Chowdhury and Arora 1982], including fish [Friedmann et al 1996;Wester and Canton 1992], birds [McNeil and Bhatnagar 1985;Maretta et al 1995], mice [Lee and Dixon 1975;Orisakwe et al 2001], rats [Massanyi et al 2007;Homma-Takeda et al 2001] and monkeys [Mohamed et al 1987]. It is important to stress that although some data is available on the effects of inorganic mercury on fertility in experimental animals [Lee and Dixon 1975;Orisakwe et al 2001;Rao 1989] the majority of works have focused on organic mercury.…”
Section: Discussionmentioning
confidence: 99%
“…The number of rat epididymal sperm declined after incubation with inorganic mercury and a dose-dependent decrease in motility was also noted [Rao and Gangadharan 2008]. Monkeys administered methyl mercury orally at 50 or 70 mg/kg/day for 155 Ambient Heavy Metal Exposure and Male Reproduction 20 weeks had non-significantly elevated blood mercury levels (approximately 2 ppm) [Mohamed et al 1987]. The percent motile sperm decreased in a dose-dependent fashion and was significantly different than the controls (approximately 58% and 52% vs. approximately 66% motile, respectively).…”
Section: Animal and In Vitro Studiesmentioning
confidence: 99%
“…[13][14][15] Reproductive toxicity of mercury has been described in several animal studies in which sperm motility, epididymal sperm count and normal sperm morphology decreased among rats, mice and monkeys after mercury exposure. [16][17][18][19][20] Human studies are few and contradictory. It has been reported that seminal fluid mercury concentrations are correlated with abnormal sperm morphology and abnormal sperm motility.…”
Section: Introductionmentioning
confidence: 99%
“…20 Adult monkeys with blood mercury levels around 2000 ng ml 21 , had a decreased sperm motility and sperm swimming speed, and increased abnormal sperm tail morphology. 17 Intraperitoneal mercury exposure at 1 mg kg 21 resulted in adverse effects on fertility among 7-week-old mice. 16 The animals and seminal fluids were exposed to significantly higher concentrations of mercury than observed in the present study.…”
mentioning
confidence: 99%